Keterlibatan TNI Dalam Penyaluran Logistik Bencana Banjir Bandang Di Aceh - Suryaningrum, Madyasari; Pusparini, Dewi Okta (PPM Sdirjianbang Akademi Militer, 2026)
The flash floods that struck Aceh Province in November 2025 devastated Aceh Province, particularly several severely affected areas. The Indonesian National Armed Forces (TNI) moved quickly to address the flood disaster. One form of their involvement was in the distribution of logistics. Several factors need to be considered in distributing logistical aid in Aceh Province to ensure its smooth operation, supported by relevant agencies such as the National Disaster Management Agency (BNPB) and the National Disaster Management Agency (BNPA). The purpose of this study was to determine the TNI's involvement in the distribution of logistics for the flash flood disaster in Aceh. This study used a qualitative literature study method with a descriptive qualitative approach. Data collection techniques used documentation. The data were obtained from official websites, national news sites, and relevant scientific journals. The results showed that the TNI's involvement significantly contributed to the smooth distribution of logistics to communities affected by the flash floods in Aceh. Transportation readiness and coordination with relevant agencies accelerated aid distribution.